Implementation of Enhanced Recovery After Caesarean Section (ERACS) in Elective Procedure : A Case Report - Sardimon Sardimon; Yusmalinda Yusmalinda; Zafrullah Khany Jasa; Rahmi Rahmi; Fauzan Bachtiar Amin (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2022)
Background: Enhanced Recovery After Cesarean Section (ERACS) protocol includes every component of the pre-operative, intra-operative and post-operative pathway. In the pre-operative phase, the protocol applied to this patient included the shortest possible fasting interval, oral intake of liquid carbohydrate and patient counselling. For intra-operative pathway, the components applied are prevention of hypotension, maintenance of normothermia, optimal uterotonic administration, IONV (intra-operative nausea and vomiting)/PONV (post-operative nausea and vomiting) prophylaxis, multi-modal analgesia and optimization of fluid administration. Post-operatively, the patient was given early nutritional intake, early mobilization, urinary catheter removal, venous thrombo-embolism prophylaxis, multi-modal analgesia and glycemic control. ERACS prove useful for early discharge, improving outcomes such as breastfeeding or reducing post-discharge opioid use.Case Illustration: A 31-year-old woman came with the chief complaint of fluid discharge since ± 3 hours prior to admission to the hospital. Based on the medical history, physical examination, and laboratory findings, the patient was diagnosed with premature rupture of membranes in a gestational age of 37-38 weeks and had a live, single-headed presentation of the fetus. Patient’s physical status is ASA II and scheduled for elective C-section procedure with spinal anesthesia.Conclusion: The implementation of the ERACS protocol in this case has been shown to reduce the rate of infection and post operative complications as well as reducing length of stay for the mother.